Characterization and classification of different female hairline patterns in the Thai population. (11th August 2020) - Natpracha, Wasrin; Sukanjanapong, Siriorn; Chanprapaph, Kumutnart; Suchonwanit, Poonkiat
Abstract: Background: The hairline is an essential component of the human face. Disfigurement of the hairline may cause physical and psychological problems. Standard guidelines do not exist for female hairline designs, average values of infratemporal portion, hairline classifications, and preferences. Aims: We aimed to study hairline characteristics in Thai females and further compare the values with previous studies in different populations. Furthermore, we aimed to introduce a comprehensive hairline classification system that allowed an easy and detailed phenotypic characterization of female hairline. Patients/Methods: Healthy Thai females aged over 18 years were included in the study. Collection of demographic data, infratemporal measurements, and standard photography was performed. All collected data were analyzed to determine the standard values of each hairline dimension for comparison to previous studies. Results: Two hundred and twenty‐nine females, with a mean age of 32.4 ± 8.6 years, participated in this study. The mean mid‐frontal line was 6.45 ± 0.89 cm, which was not correlated with age. Lateral mounds, widow's peaks, and cowlicks were observed in 42.35%, 24.45%, and 1.74% participants, respectively. Our study revealed five patterns of the frontal hairline and four patterns of the temporal hairline. The mid‐frontal line in Asian females trended longer than that in Caucasians, without statistical significance. Conclusions: Measurements of the infratemporal portions in Thai females revealed no change with age, and the mid‐frontal line showed no statistically significant differences between Korean and Turkish participants. The hairline classification system introduced in our study was comprehensive and would be easily applicable in clinical practice. Female hairline dimensions and patterns reported in our study could provide reference values for hairline design in hairline restoration surgery as well as assist in accurate diagnosis of hair disorders.